A new method for overpressure mechanisms analysis - Satti, I.A. (Society of Petroleum Engineers, 2015)
The knowledge of overpressure mechanisms is an important prerequisite of overpressure prediction. The mechanisms of overpressure can be identified using the pre-existing techniques of cross plotting the velocity versus effective stress and density. However, this paper discusses a new method of overpressure mechanisms analysis using the acoustic impedance. The acoustic impedance is calculated using sonic velocity and density log. The acoustic impedance log shows clear change in trend with increase in overpressure generated by fluid expansion mechanisms. Based on the change in trend of acoustic impedance, a relationship has been developed between acoustic impedance and mechanisms of overpressure. Copyright 2015, Society of Petroleum Engineers.